Incidence of Facial Palsy Following Microsurgical Removal of Vestibular Schwannoma Using Direct Electrical Stimulation: a Meta-Analysis - Ekaterina G. Seliverstova; Mikhail V. Sinkin; Andrey A. Grin (Анналы клинической и экспериментальной неврологии)
Aim. To determine the incidence of facial palsy (FP) following microsurgical removal of vestibular schwannoma using direct electrical stimulation.